SISTEM INFORMASI PROGRAM KERJA PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA (PKK) Di Desa Cabean, Kecamatan Cepu, Kabupaten Blora - Joko Handoyo; Joko Handoyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
PKK (Empowerment and Family Welfare) is a national movement in community development that grows from below, where the management is carried out by the surrounding community for mutual welfare. There are 4 working groups in the Cabean Village PKK program, namely: PokJa 1 includes: (religious, social, mutual cooperation), PokJa 2 includes: (UP2K, UPPKS, BKB, BKR, BKL), PokJa 3 includes: (clothing, food, yard land use), and PokJa 4 include: (health, posyandu, posbindu). In the PKK administration process in Cabean Village, they still use manual methods both in recording data and conducting data recapitulation. This causes several problems that often become obstacles in the PKK administration process in Cabean Village. The purpose of this research is to build an information system for PKK work programs that are expected to be able to solve problems related to the quality of information, in the form of: the availability of information in computerized form so that it can be obtained quickly. From the data taken from the Cabean Village PKK, which includes: membership data, work program data, training activity data, and annual report data. The information system design is modeled into diagrams in the UML (Unified Modeling Language) and the System Development Life Cycle (SDLC) development method with the Waterfall model. SDLC means creating a new system to replace the old system as a whole or improve an existing system to be structured. From the results of the functionality test, it was obtained 93,3% of the average feasibility of the test so that it was feasible to be used or applied to the information system. The Information System for the Work Program for Empowerment and Family Welfare (PKK) in Cabean Village has succeeded in inputting 20 records and the stages of work carried out by the information system analysis and programmers in building the information system.